(untitled) (Biological Sciences - PJSIR, 2020)
The study was conducted at Arid Zone Research Centre (AZRC), Dera Ismail Khan (D.I.Khan) to evaluate cost and benefit of wheat cultivation in district Dera Ismail Khan, Khyber Paktoon Khwa province of Pakistan during 2015. The basic underlying assumption of economic analysis of wheat production was to assess the farmers/growers financial impact of wheat cultivation. A sample of 200 respondents from 10 major wheat growing villages of the respective areas of the district was interviewed through pretested questionnaire. The study revealed that the cost of wheat production was Rs=35,680 per acres, whereas output comes 1650 Kg per acre (42 mounds) amounting Rs=63,600 per acre. Farmers’ margin also rises by adding the value of family labour and owned land which is sufficient to sustain a normal family. Moreover, positive influence between return price and output of wheat was concluded from the study, whereas negative effect of cost was also observed. The output elasticity of Land Preparation (LP), Seed and Sowing (SS), Farm Inputs (FI), Irrigation (Irr), Pesticides (Pest) and Harvesting/Threshing (HT) are 0.124587, 0.31244, 0.5874, 0.55461, 0.08248 and 0.65743, respectively.